PELAYANAN PASTORAL PRANIKAH PERNIKAHAN DAN KELUARGA KRISTEN DALAM MENCAGAH TERJADINYA KONFLIK - Sem Irfan Patabang (ADIBA : JOURNAL OF EDUCATION, 2026)
Pastoral care is essential for accompanying prospective brides and grooms until marriage. This study aims to examine how holistic pastoral care can prepare couples before marriage, strengthen marital relationships, and foster Christian families so they can wisely navigate various conflicts. This study employed a literature study method, reviewing various sources, including books, scientific journals, and the Bible as its primary reference. The results indicate that premarital pastoral care can assist the emotional and spiritual readiness of prospective couples before marriage. During marriage, pastoral care plays a role in fostering commitment and fidelity in resolving conflicts. Pastoral care in Christian families emphasizes the family's function as a small church based on love, enabling them to effectively resolve conflicts. Therefore, pastoral care is essential from the premarital period through marriage to marriage, preventing conflict and divorce and fostering a harmonious and mature household based on the Christian faith.